Access and reimbursement pathways for digital health solutions and in vitro diagnostic devices: Current scenario and challenges - Mantovani, Andrea; Leopaldi, Claudia; Nighswander, Cassandra Maria; Di Bidino, Rossella (Frontiers in Medical Technology, 2023)
Objectives Digital therapeutics (DTx) are innovative solutions that use meaningful data to provide evidence-based decisions for the prevention, treatment, and management of diseases. Particular attention is paid to software-based in vitro diagnostics (IVDs). With this point of view, a strong connection between DTx and IVDs is observed. Methods We investigated the current regulatory scenarios and reimbursement approaches adopted for DTx and IVDs. The initial assumption was that countries apply different regulations for the access to the market and adopt different reimbursement systems for both DTx and IVDs. The analysis was limited to the US, European countries (Germany, France, and UK), and Australia due to maturity in digital health product adoption and regulatory processes, and recent regulations related to IVDs. The final aim was to provide a general comparative overview and identify those aspects that should be better addressed to support the adoption and commercialization of DTx and IVDs. Results Many countries regulate DTx as medical devices or software integrated with a medical device, and some have a more specific pathway than others. Australia has more specific regulations classifying software used in IVD. Some EU countries are adopting similar processes to the Digital Health Applications (DiGA) under Germany's Digitale-Versorgung Gesetz (DVG) law, which deems DTx eligible for reimbursement during the fast access pathway. France is working on a fast-track system to make DTx available to patients and reimbursable by the public system. The US retains some coverage through private insurance, federal and state programs like Medicaid and Veterans Affairs, and out-of-pocket spending. The updated Medical Devices Regulation (MDR) and In Vitro Diagnostic Regulation (IVDR) in the EU includes a classification system specifying how software integrated with medical devices, and IVDs specifically must be regulated. Conclusion The outlook for DTx and IVDs is changing as they are becoming more technologically advanced, and some countries are adapting their device classifications depending on specific features. Our analysis showed the complexity of the issue demonstrating how fragmented are regulatory systems for DTx and IVDs. Differences emerged in terms of definitions, terminology, requested evidence, payment approaches and the overall reimbursement landscape. The complexity is expected to have a direct impact on the commercialization of and access to DTx and IVDs. In this scenario, willingness to pay of different stakeholders is a key theme.